2022
DOI: 10.1002/ccr3.5756
|View full text |Cite
|
Sign up to set email alerts
|

Use of the flexible bronchoscope and Infrared Red Intubation System in a known difficult airway in the intensive care unit

Abstract: This case report describes a patient in the ICU in need of urgent intubation, for whom video laryngoscope‐guided intubation had previously failed. The Infrared Red Intubation System (IRRIS) may enhance the chance of successful flexible bronchoscope intubation, especially when performed by non‐expert anesthesiologists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…We found six reports on the clinical use of IRRIS in the literature 5,7,22–25 . Four were case reports, 24,25 or smaller retrospective case series, demonstrating the applicability of the technique for awake video‐bronchoscope‐guided intubation in patients with difficult 5,24,25 or extremely difficult 7 airways, and two reports demonstrated its successful use for rigid video‐laryngoscopic intubation in lean 23 and obese 22 patients without airway pathology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found six reports on the clinical use of IRRIS in the literature 5,7,22–25 . Four were case reports, 24,25 or smaller retrospective case series, demonstrating the applicability of the technique for awake video‐bronchoscope‐guided intubation in patients with difficult 5,24,25 or extremely difficult 7 airways, and two reports demonstrated its successful use for rigid video‐laryngoscopic intubation in lean 23 and obese 22 patients without airway pathology.…”
Section: Discussionmentioning
confidence: 99%
“…We found six reports on the clinical use of IRRIS in the literature 5,7,22–25 . Four were case reports, 24,25 or smaller retrospective case series, demonstrating the applicability of the technique for awake video‐bronchoscope‐guided intubation in patients with difficult 5,24,25 or extremely difficult 7 airways, and two reports demonstrated its successful use for rigid video‐laryngoscopic intubation in lean 23 and obese 22 patients without airway pathology. In our prospective randomised study, we found that the infrared flashing light is an effective and easily applicable adjunct for awake flexible bronchoscope‐guided intubation in airway scenarios that are difficult due to the presence of airway pathology.…”
Section: Discussionmentioning
confidence: 99%